2020
DOI: 10.1108/ccij-01-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Building organizational trust through internal communication

Abstract: PurposeAlthough multiple research studies disclosed that internal communication is effective in building trust within organizations, the link between employees' satisfaction with internal communication and their trust in their employers has not been explored. The paper explores the interrelationship between eight facets of internal communication satisfaction (ICS) and five dimensions of organizational trust (OT).Design/methodology/approachThe quantitative questionnaire-based field research was conducted on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Some research reports that internal communication plays an essential role in the organization ( Meng & Berger, 2012 ; Thornton, 2018 ). It significantly influences employees’ trust, satisfaction, commitment, loyalty ( Asif & Sargeant, 2000 ; Mazzei, 2014 ; Pološki Vokić et al, 2020 ), employee participation, and job satisfaction ( Ćorić et al, 2020 ). Internal communication also encourages employee performance ( Ćorić et al, 2020 ), strengthens employee commitment, promotes a positive sense of organizational belonging, develops employees’ awareness of environmental change, and develops employees’ understanding of the organization's needs ( Mazzei, 2010 ; Welch & Jackson, 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Some research reports that internal communication plays an essential role in the organization ( Meng & Berger, 2012 ; Thornton, 2018 ). It significantly influences employees’ trust, satisfaction, commitment, loyalty ( Asif & Sargeant, 2000 ; Mazzei, 2014 ; Pološki Vokić et al, 2020 ), employee participation, and job satisfaction ( Ćorić et al, 2020 ). Internal communication also encourages employee performance ( Ćorić et al, 2020 ), strengthens employee commitment, promotes a positive sense of organizational belonging, develops employees’ awareness of environmental change, and develops employees’ understanding of the organization's needs ( Mazzei, 2010 ; Welch & Jackson, 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internal communications can be viewed as a form of relationship-building ( Asif & Sargeant, 2000 ). By implementing two-way symmetrical internal communication, employees feel that they can express their thoughts ( Mazzei, 2010 ; Sedej & Justinek, 2013 ), their voices are heard, and they are empowered ( Pološki Vokić et al, 2020 ). Therefore, internal communication functions to maintain the relationship with internal stakeholders in the organization through sharing and receiving the information, including downward, upward, and horizontal communication ( Ćorić et al, 2020 ), and communicative actions represent a behavioral outcome of loyalty ( Mazzei, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, research in management and social sciences [3,4] has shown that organizational trust can be considered a source of competitive advantage and a prerequisite for the efficient functioning of organizations and HRM [5]. Moreover, trust within organizations is critical to the performance and wellbeing of their employees [6,7], and it may foster innovative and prosocial behaviors that help to create financial advantages as well [8,9].…”
Section: Introductionmentioning
confidence: 99%